Clinical use of biomarkers in neurodegenerative disorders - Manuel Menendez-Gonzalez (Frontiers Research Topics, 2014)
The prevalence of neurodegenerative disorders is increasing dramatically and one of the major challenges today is the need of early and accurate diagnosis, the other is the need of more effective therapies -in turn the development of such therapies also requires early and accurate diagnosis-. The main hope for an earlier and more accurate diagnosis comes from the use of biomarkers. Much research is being done trying to solve the many interrogates related to the role of biomarkers in clinical practice, including the early diagnosis, differential diagnosis and follow-up of neurodegenerative disorders. This is a field where translational research is intense enough to make this topic interesting for basic researchers and clinicians. Indeed, the amount and quality of articles received in response to the call for contributions was very good. This eBook contains a good amount of high quality articles devoted to diverse techniques across several neurodegenerative disorders from different perspectives, including original reports, reviews, methods reports and opinion letters on biochemical biomarkers in biological fluids, neuroimaging techniques and multidimensional approaches linking clinical findings with biomarkers. The disorders covered are also diverse: Alzheimer's disease, Frontotemporal Dementia, Dementia with Lewy Bodies, Huntington's disease, Parkinson's disease among others. As we can learn from articles in this Research Topic, biomarkers are allowing us to expand the knowledge on the biological and anatomical basis of neurodegenerative diseases and to implement diagnostic techniques in clinical practice and clinical trials.